Strategi Pembelajaran Blended Learning terhadap Motivasi, Hasil, dan Mutu Belajar Mahasiswa - Sabda Dian Nurani Siahaan; Dodi Pramana (Ekuitas: Jurnal Pendidikan Ekonomi, 2020)
The purpose of this study is to analyze the implementation of Blended Learning on the Motivation, Outcomes, and Learning Quality of students in the Department of Economics, Universitas Negeri Medan, academic year 2019/2020. The students’ Learning Outcomes studied are Entrepreneurship. The method used in this study is descriptive quantitative. The population in this study was Department of Economics students class of 2017 totaling 295 people consisting of 3 study programs : Economic Education, Business Education, and Office Administration Education. The sample used was 236 people by adopting a purposive sampling technique. The results show that the Implementation of Blended Learning are in Good category. Motivation and Student Learning Quality are also in Good category. On the Learning Outcomes variable, students generally get mastery grades in Entrepreneurship courses. The results also show the Implementation of Blended Learning strategies has a positive and significant effect on Motivation, Learning Outcomes, and Learning Quality. The better the implementation of Blended Learning, both in design and facilities, then the Motivation, Outcomes, and Learning Quality of students will also increase.